2021
DOI: 10.3389/fimmu.2021.801281
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Fatal Complications of BK Virus-Hemorrhagic Cystitis and Severe Cytokine Release Syndrome Following BK Virus-Specific T-Cells

Abstract: BK virus (BKV)-hemorrhagic cystitis (HC) is a well-known and rarely fatal complication of hematopoietic stem cell transplantation (HSCT). Treatment for BKV-HC is limited, but virus-specific T-cells (VST) represent a promising therapeutic option feasible for use posttransplant. We report on the case of a 16-year-old male with dedicator of cytokinesis 8 (DOCK8) deficiency who underwent haploidentical HSCT complicated by severe BKV-HC, catastrophic renal hemorrhage, and VST-associated cytokine release syndrome (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…[23,24] However, efficacy of such a therapy has to be balanced with risks of potential immune-mediated side effects (such GVHD, immune reconstitution syndrome, cytokine release syndrome) and elevated health care costs. [23,25] The main adverse event of EV cidofovir in our patients was bladder spasms and/or pain. Such discomfort was similarly reported in about 30% of cases in other case series.…”
Section: Discussionmentioning
confidence: 85%
“…[23,24] However, efficacy of such a therapy has to be balanced with risks of potential immune-mediated side effects (such GVHD, immune reconstitution syndrome, cytokine release syndrome) and elevated health care costs. [23,25] The main adverse event of EV cidofovir in our patients was bladder spasms and/or pain. Such discomfort was similarly reported in about 30% of cases in other case series.…”
Section: Discussionmentioning
confidence: 85%
“…Phase-2 studies based on third-party or donor-derived T-lymphocytes demonstrated satisfactory response rates in absence of infusion toxicity and with 1 reported onset of grade 2 skin GvHD (33,34), but a 16-year old HCT patient due to DOCK8 de ciency complicated by HC and high BKPyV viremia suffered from signi cant cytokine release syndrome (35). 9) Adoptive cell therapy is an area of investigation and future research.…”
Section: ) Intravesical CDV Represents An Area Of Clinical Researchmentioning
confidence: 99%
“…It is worth noting that rare but serious adverse effects of VST, including cytokine release syndrome, diffuse alveolar damage, hepatic sinusoidal obstruction syndrome, multi-organ failure[ 53 ], and GVHD[ 52 ] have been reported in literature. Other potential logistical limitations of VST include the need for donor immunity to the viral target, as well significant cost, labor, time, and regulatory burden for manufacturing the therapy[ 52 , 54 ].…”
Section: Vstmentioning
confidence: 99%